# Convert the equation 3x - 4y - 12 = 0, into slope intercept form and intercept-intercept form?

### 1 Answer | Add Yours

The equation of a line ax + by + c = 0 can be converted into slope-intercept form as y = m*x + c where m is the slope and c is the y-intercept. If the line is converted to the form x/a + y/b = 1, it is in intercept-intercept form with a and b being the x and y intercepts respectively.

The line we have here is 3x - 4y - 12 = 0

3x - 4y - 12 = 0

=> 4y = 3x - 12

=> y = (3/4)x - 3

the slope is 3/4 and the y-intercept is -3

3x - 4y - 12 = 0

=> 3x - 4y = 12

=> (3/12)x + (-4/12)y = 1

=> x/4 - y/3 = 1

The x intercept is 4 and the y-intercept is -3

**The equation in the slope-intercept form is y = (3/4)x - 3 and in the intercept-intercept form is x/4 - y/3 = 1**